Structural geology and gold mineralisation of the Ora Banda and Zuleika districts, Eastern Goldfields, Western Australia. - Tripp, Gerard I. (Curtin University, 2000)
Late-Archaean deformation at Ora Banda 69km northwest of Kalgoorlie, Western Australia, resulted in upright folds (D2), ductile shear zones (D3), and a regional-scale brittle-ductile fault network (D4). Early low-angle faults (D', D1), documented in the surrounding Coolgardie, Kambalda and Boorara Domains are not developed in the Ora Banda Domain, and the fabrics reflect only the latest ENE-WSW shortening event. The western limb of the regional-scale ESE- plunging Kurrawang syncline (D2), is truncated by the Zuleika Shear Zone (D3), a within- greenstone ductile shear zone located 10km southeast of Ora Banda. The shear zone has a much greater strike length (250km) than depth extent, as seismic imagery reveals a sharp truncation against a mid-crustal decollement at a depth of 6km-depth below surface. The Zuleika Shear Zone is a NW-SE trending band of anastomosing S-C mylonite zones formed in conjugate sets of NW- SE trending sinistral and N-S trending dextral shear zones. Widely distributed flattening strains and more restricted zones of non-coaxial shear in the Zuleika Shear Zone, suggest deformation-path partitioning typical of a transpressional tectonic environment. Latetectonic brittle-ductile faults (D4) cross-cut the Zuleika Shear Zone and surrounding greenstones, and hence are not Riedel structures or other lower order faults genetically related to the ductile shearing. Gold mineralisation of the Zuleika Shear Zone began during the ductile deformation (D3), continued through peak metamorphism that postdates the shearing, and finally ceased after the brittle-ductile faulting event (D4). Gold deposits are primarily located where brittle-ductile faults intersect the Zuleika Shear Zone.Brittle-ductile faults (D4), are developed in three principal structural orientations: N-S (dextral), NE-SW (dextral) and E-W (sinistral). These faults display mutual cross-cutting relationships and were formed synchronously during a single regional shortening event. The brittle-ductile fault network is developed unevenly over the region, being localised in packets of high fracture-density referred to as structural zones. The Ora Banda structural zone is an area of high density faulting in the vicinity of Ora Banda, composed of a network of interlinked faults in which alternating ductile and brittle conditions produced cataclasite, breccia and quartz vein systems overprinting mylonite and schistosity. Other areas of high fracture-density (eg. Grants Patch and Mount Pleasant structural zones), are located within the NW-SE trending Ora Banda mafic sequence and spaced at 10km intervals to the southeast of Ora Banda. This spatial periodicity of high fracturedensity within the mafic sequence may have developed as a result of layer-parallel extension during ENE- WSW regional shortening. Gold deposits are concentrated in the Ora Banda, Grants Patch and Mount Pleasant structural zones. Gold distribution within the Ora Banda structural zone traces out the distribution of brittle-ductile faults, indicating that the fault network was the major pathway for fluid flow during mineralisation. Hydrothermal minerals are integral components of fault fabrics within the structural zone, and textures indicate that the faults were formed under conditions of high fluid pressure and, for much of the deformation, may have been fluid-generated.At Ora Banda the Enterprise gold deposit (40 tonnes Au) highlights the control of mesoscopic- scale fractures on gold distribution. On aeromagnetic imagery, the Enterprise fault zone appears as a narrow fault structure, but at a mesoscopic-scale, it is a broad zone of interlinked brittle-ductile faults and quartz veins. Fabrics developed in the layered, differentiated dolerite host rocks of the Enterprise fault zone, range from cataclasite to banded mylonite with a major component of net- veined breccia (mesofracturing). Kinematic analyses of fault slip lineations reveal an 055 directed (ENE-WSW) maximum shortening axis during brittle-ductile faulting. Microfabrics of the faults show extensive recrystallisation with significant post-deformation recovery that may be related to late to post - tectonic intrusion of the adjacent Lone Hand Monzogranite. Deformation mechanisms indicate that the D4 event occurred at a low-to-moderate temperature, in a low strain-rate enviromnent typical of mid to upper-greenschist facies crustal conditions. Gold mineralisation in the Enterprise deposit is controlled by faults with high-grade shoot development at the intersection of faults and host rock contacts that may represent gradients in tensile rock-strength. Although gold distribution indicates that faults are a major control on mineralisation, at a microscopic-scale, the control is by a linked network of microfractures that pervades the host rocks.Fry analysis of gold deposits within the Ora Banda mafic sequence shows clustering into groups with about 10km spacing. Coincidence of high fracture-density zones and gold deposits in 1Okm spaced-corridors reveals the regional-scale nature of gold mineralisation within the brittle-ductile fault network. Fluid-pressure gradients generated by pressure release during high-density fracturing, may have effectively increased fluid-rock ratios by focussing of metamorphic fluids through these areas. The largest gold deposits in the Ora Banda mafic sequence are hosted by 060-090 trending brittle-ductile faults with dilational textures (hydraulic breccia), and minor evidence of slip with negligible offsets. The orientation of these structures is sub-parallel to the regional axis of maximum shortening, hence an environment of fluid overpressuring in the presence of a far-field stress system produced conditions where fluid pressure is greater than or equal to the combined minimum compressive stress and the tensile rock strength. Such conditions are conducive to multiple failure episodes with fluid-pressure cycling and transient permeability as a consequence of fault reactivation. Formation of the brittle-ductile fault network occurred as a result of a delicate balance between deviatoric stress and fluid pressure, hence incremental fault development contributed to, and was a consequence of, the gold mineralisation event.The geometric relations of shear zones, brittle-ductile faults and gold mineralised zones are similar across all scales of observation from regional to microscopic and are therefore fractal. Fractal geometry indicates that deformation and gold mineralisation are temporally and genetically associated, and this combined with the textural relationships of the gold ores indicates that the sites of gold deposition were not structurally prepared prior to mineralisation. Development of early ductile to later brittle-ductile structures indicates changing conditions of deformation typical of decreasing crustal depth, or a variation of strain rate with time. The lack of a significant change in orientation of the maximum shortening direction and continuance of gold mineralisation throughout ductile and brittle deformation events, implies that deformation was progressive during a bulk shortening that accompanied uplift of the crust.